2011
DOI: 10.1038/ni.2045
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells mediate influenza-induced airway hyper-reactivity independently of adaptive immunity

Abstract: Patients with asthma, a major public health problem, are at high risk for serious disease from influenza virus infection, but the pathogenic mechanisms by which influenza A causes airway disease and asthma are not fully known. We show here in a mouse model that influenza infection acutely induced airway hyper-reactivity (AHR), a cardinal feature of asthma, independently of T helper type 2 (TH2) cells and adaptive immunity. Instead, influenza infection induced AHR through a previously unknown pathway that requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
762
7
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 704 publications
(807 citation statements)
references
References 40 publications
23
762
7
8
Order By: Relevance
“…The ILC family now includes ILC1 (predominantly IFN-g-expressing cells), ILC2 (predominantly IL-5-and IL-13-expressing cells), and ILC3 (predominantly IL-22-and IL-17-expressing cells) (3)(4)(5)(6). Due to their recent discovery, our knowledge of these cells is still rather rudimentary, but major roles are emerging for ILCs in protective immunity against parasitic helminths (ILC2) (7)(8)(9) and bacteria (ILC1 and ILC3) (10)(11)(12), and in autoimmune disorders (ILC1 and ILC3) (13), allergic disease (ILC2) (14)(15)(16), and obesity (17)(18)(19).…”
mentioning
confidence: 99%
“…The ILC family now includes ILC1 (predominantly IFN-g-expressing cells), ILC2 (predominantly IL-5-and IL-13-expressing cells), and ILC3 (predominantly IL-22-and IL-17-expressing cells) (3)(4)(5)(6). Due to their recent discovery, our knowledge of these cells is still rather rudimentary, but major roles are emerging for ILCs in protective immunity against parasitic helminths (ILC2) (7)(8)(9) and bacteria (ILC1 and ILC3) (10)(11)(12), and in autoimmune disorders (ILC1 and ILC3) (13), allergic disease (ILC2) (14)(15)(16), and obesity (17)(18)(19).…”
mentioning
confidence: 99%
“…NH cells can produce large amounts of type-2 cytokines such as IL-5 and IL-13 in response to IL-33. Several groups have characterized populations of type-2 cytokine-producing ILCs associated with IL-33 mediate diseases in the lung [15][16][17][18][19][20][21] . However, it is unknown whether NH cells are involved in the observed corticosteroid sensitivity.…”
mentioning
confidence: 99%
“…A number of groups have demonstrated the role of ILC2 as key producers of type 2 cytokines in several different experimental lung inflammation models (Barlow et al 2012Bartemes et al 2012;Chang et al 2011;Kim et al 2012;Scanlon and McKenzie 2012;Walker and McKenzie 2013). The activation of ILC2 within lungs is very rapid, with high levels of IL-5 and IL-13 production within 12 h of exposure of mice to the fungal allergen Alternaria alternata (Bartemes et al 2012).…”
Section: Role Of Ilc2 In the Pathogenesis Of Allergic Inflammationmentioning
confidence: 99%
“…Chang et al (2011) showed that ILC2, activated by macrophagederived IL-33, were sufficient to drive influenza-induced airway hyperresponsiveness (AHR) in mice. This effect was mediated by ILC2-derived IL-13, since adoptive transfer of wild-type ILC2 into infected il13 -/-mice was sufficient to restore viral-induced AHR in these otherwise AHR-resistant mice (Chang et al 2011).…”
Section: Role Of Ilc2 In the Pathogenesis Of Allergic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation